An Interactive Web-Gis Development for Risk Tsunami Hazard Potential Information In Pangandaran Village West Java - Andrian, Juan; Ismail, Arif; Setiawan, Iwan; Himayah, Shafira (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
In 2006, a tsunami disaster occurred on the coast of Pangandaran Regency which claimed up to 664 fatalities. A large number of people died due to lack of information in knowing areas that are prone to tsunami disasters. Therefore, a geographic information system for the tsunami disaster is needed to facilitate the Pangandaran community to find out areas that are prone to tsunami disasters. In making a geographic information system web tsunami disaster using GeoServer, PostgreSQL and LeafletJS. Making a geographic information system web is done in several ways, namely, entering shapefile data into a database and then displaying it on a map server. The results of creating a web of the tsunami geographic information system contain information on land use, public facilities, hamlet boundaries, road networks, river networks and tsunami disaster mitigation.